Patient recommendations for opioid prescribing in the context of HIV care: findings from a set of public deliberations. Issue 11 (1st November 2020) - Scherer, Maya; Weiss, Linda; Kamler, Alexandra; George, Mary-Catherine; Navis, Allison; Gebhardt, Yves; Robinson-Papp, Jessica
ABSTRACT: It is widely acknowledged that the growing opioid epidemic and associated increase in overdose deaths necessitates a reexamination of processes and procedures related to an opioid prescription for the treatment of chronic pain. However, the perspectives of patients, including those at the highest risk for opioid-related harms, are largely missing from this reexamination. To partially address the gap, we conducted a pair of one-day public deliberations on opioid prescribing in the context of HIV care. Results included recommendations and perspectives from people living with HIV that detail how providers can best assess patient needs, communicate regarding opioids, and reduce the risk of misuse. Participants emphasized the importance of building trust with patients and taking an extensive patient history prior to making decisions about whether to initiate or end an opioid prescription. This trust – together with an understanding of the origin of a patient's pain, history of drug use and other therapies tried – was perceived as essential to effective monitoring and pain management, as well as promotion of positive health outcomes. Ensuring that such patient perspectives are incorporated into the operationalization of guidelines for safe opioid prescribing may help to improve outcomes and quality of care for people living with HIV.